Quality of life in patients with head and neck cancer receiving targeted or multimodal therapy: update of the EORTC QLQ-H&N35, phase I - Singer, Susanne; Arraras, Juan I.; Baumann, Ingo; Boehm, Andreas; Chie, Wei-Chu; Galalae, Razvan; Langendijk, Johannes A.; Guntinas-Lichius, Orlando; Hammerlid, Eva; Pinto, Monica; Nicolatou-Galitis, Ourania; Schmalz, Claudia; et al. (Head & neck, 2013)
Background The objective of this study was to identify relevant quality of life (QOL) issues in patients with head and neck cancer receiving multimodal and/or targeted therapies. Methods The literature was searched for QOL issues reported after multimodal and/or targeted therapies resulting in a list of potentially relevant issues. These were discussed within a multiprofessional expert group, revised, and subsequently rated for relevance by patients and health care providers. Results Twenty-seven issues were extracted that are not covered by the current version of the European Organization for Research and Treatment of Cancer (EORTC) questionnaires. Interviews (96 health care providers from 13 countries, 137 patients from 8 countries) revealed that 26 of these issues were relevant for patients with head and neck cancer. Conclusions Studies investigating targeted and/or multimodal therapy should consider that some QOL issues specific to these treatments are not covered by the current version of the EORTC instruments. Consequently, the EORTC head and neck cancer module is currently in revision. © 2012 Wiley Periodicals, Inc. Head Neck, 2013